IDENTIFIKASI KELEMBAGAAN PERTANIAN DAN PERANANNYA PADA SUBSISTEM PRODUKSI TANAMAN PADI SAWAH DI DESA BUKIT PARIAMAN KECAMATAN TENGGARONG SEBERANG - Mariyah, Mariyah; Mariati, Rita; Yulianto Arifin, Eko Harri; Khairani, Adinda Rizky (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
Agricultural Institutions are a driving factor in achieving agricultural resource management that encourages the achievement of farmer welfare. The existence of important physical and management aspects is studied, especially in rice producing centers, in relation to their contribution to the food supply. The objective of this research to identify existing agricultural institutions in Bukit Pariaman Village, to identify the role of farming institutions in the rice farming production subsystem, and analyze farmers' access to existing agricultural institutions in Bukit Pariaman Village. The research was conducted in Bukit Pariaman Village, Tenggarong Seberang District, Kutai Kartanegara Regency in May-July 2024. The sampling method was purposive sampling. Data analysis used descriptive analysis and perception analysis of access to agricultural institutions. The research results showed that agricultural institutions in Bukit Pariaman Village are adequate and well accessible. The role in the production subsystem was demonstrated by the achievement of an annual rice production surplus of 88.81%.